Colletotrichum higginsianum as a Model for Understanding Host–Pathogen Interactions: A Review - Yan, Yaqin (Int J Mol Sci, 2018)
Colletotrichum higginsianum is a hemibiotrophic ascomycetous fungus that causes economically important anthracnose diseases on numerous monocot and dicot crops worldwide. As a model pathosystem, the Colletotrichum–Arabidopsis interaction has the significant advantage that both organisms can be manipulated genetically. The goal of this review is to provide an overview of the system and to point out recent significant studies that update our understanding of the pathogenesis of C. higginsianum and resistance mechanisms of Arabidopsis against this hemibiotrophic fungus. The genome sequence of C. higginsianum has provided insights into how genome structure and pathogen genetic variability has been shaped by transposable elements, and allows systematic approaches to longstanding areas of investigation, including infection structure differentiation and fungal–plant interactions. The Arabidopsis-Colletotrichum pathosystem provides an integrated system, with extensive information on the host plant and availability of genomes for both partners, to illustrate many of the important concepts governing fungal–plant interactions, and to serve as an excellent starting point for broad perspectives into issues in plant pathology.